2008
DOI: 10.2147/ibpc.s3809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dyslipidemia on cardiovascular risk stratification of hypertensive patients and association of lipid profile with other cardiovascular risk factors: results from the ICEBERG study

Abstract: Background: Hypertension, dyslipidemia, and other cardiovascular risk factors are linked epidemiologically, clinically, and metabolically. Intensive/Initial Cardiovascular Examination regarding Blood Pressure levels, Evaluation of Risk Groups (ICEBERG) study focuses on the effect of dyslipidemia on cardiovascular risk evaluation and association of lipid profi le with other risk factors. Patients and methods:The ICEBERG study consisted of two sub-protocols: ICEBERG-1, conducted at 20 university hospitals (Refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Our results are in agreement with those of previously conducted studies [15,16]. Given the high concomitant prevalence of hyperlipidaemia and hypertension observed in this and other studies [2,3], further research is warranted to assess the BP-lowering effect of statins in addition to standard hypertensive treatment and to develop more effective multidisciplinary management of patients with both dyslipidaemia and hypertension.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with those of previously conducted studies [15,16]. Given the high concomitant prevalence of hyperlipidaemia and hypertension observed in this and other studies [2,3], further research is warranted to assess the BP-lowering effect of statins in addition to standard hypertensive treatment and to develop more effective multidisciplinary management of patients with both dyslipidaemia and hypertension.…”
Section: Resultssupporting
confidence: 92%
“…for cardiovascular disease (CVD) and coexist in a substantial proportion of patients [1][2][3]. It has also been shown that the coronary heart disease (CHD) risk in patients with hypertension and dyslipidaemia is greater than the sum of CHD risks for hypertension and dyslipidaemia when they occur alone [4], thereby supporting a degree of clinical interaction between the two risk factors.…”
mentioning
confidence: 99%
“…Comparing levels of TC in other countries of Europe on average 61% (54% men, 66% women) of patients has TC rate higher than 5 mmol/l, however Lithuania still has the highest prevalence. According to the statistics of the American Heart Association, 15% of patients had total cholesterol levels exceeding 6 mmol/l [15]. GENOA study has shown an increase in the rate of LDL cholesterol, which depending on gender and race varied from 59.6 to 75.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Each 1 mg/dL decrease in HDL cholesterol has been shown to increase risk for coronary artery disease by 2% in men and 3% in women. The Veterans Affairs High-Density Lipoprotein Cholesterol Interventional Trial, investigating the impact of fibrate therapy on cardiovascular risk, demonstrated that 6% increase in HDL cholesterol was associated with a 22% decrease in coronary events (Kabakci et al, 2008). In addition, Lp(a) has been shown to be an independent risk factor for atherosclerosis (Hakim et al, 2008) and has been found to exert a broad variety of pro-atherogenic and pro-thrombotic properties (von Eckardstein et al, 2001).…”
Section: Discussionmentioning
confidence: 99%